Research on the Algorithm for Composite Lining of Deep Buried Water Conveyance Tunnel - Fei Li; Ningdong Chang; Jianhui Wang; Tao Feng; Chunling Li (Advances in Civil Engineering)
Composite lining of deep buried water conveyance tunnel for bearing high internal water pressure is a new type of applicable structure. However, up to date, no effective method is available to calculate the stress of the structure. In this paper, a simplified algorithm, which can be used to calculate the stress distribution of composite lining accurately but costs little computational resource, is proposed. This algorithm, which is based on the elastic theory, takes the effect of internal water pressure and surrounding rock on the composite lining into consideration, respectively. Then, the stress distribution of composite lining in infinite body is derived on the basis of Lame solution. Finally, a case study is followed by choosing a typical section of the Eastern Canal in Beijing of the South-to-North Water Diversion Project (SNWDP). This case study was analysed by using the simplified algorithm and verified by finite element method with ABAQUS. The results show that the stress distribution of composite lining can be obtained quickly and accurately with the simplified algorithm, which can provide a reference for other engineering designs.